HIV prevalence and related risk factors among male sex workers in Shenzhen, China: results from a time–location sampling survey. Issue 1 (22nd October 2009) - Cai, Wen-De; Zhao, Jin; Zhao, Jin-Kou; Raymond, H F; Feng, Yu-Ji; Liu, Jie; McFarland, Willi; Gan, Yong-Xia; Yang, Zheng-Rong; Zhang, Yan; Tan, Jing-Guang; Wang, Xiao-Rong; et al.
Abstract : Background: HIV transmission among men who have sex with men has recently become a major concern in China. Little is known, however, about HIV transmission among male sex workers (MSW). This study aimed to investigate HIV infection prevalence and risk factors among MSW in Shenzhen, China. Materials and methods: Following formative research, a cross-sectional study was conducted using time–location sampling among MSW in Shenzhen, from April to July 2008. Behavioural and serological data on HIV and syphilis were collected. The risk factors for HIV infection were analysed using a logistic regression model. Results: In total, 394 MSW were recruited for the survey. The prevalence of HIV and syphilis among these workers was 5.3% and 14.3%, respectively. Only a quarter of the MSW self-identified as homosexual. More than 70% had sex with both men and women. HIV-related knowledge levels were high regardless of HIV serostatus. Consistent condom use was low (37.1%) and varied by type of sexual partner. Factors including more non-commercial male partners, working in small home-based family clubs, being drunk before sexual intercourse, having a history of HIV tests, syphilis infection and a short period of residence in Shenzhen were associated with an increased risk of HIV infection. Conclusions: High-risk sexual practices were common among MSW regardless of their high level of HIV awareness. The working venues were associated with HIV infection and a recent test for HIV was a potential predictor of HIV infection. The time–location sampling method was found to be an appropriate way of recruiting MSW for this study, especially those without fixed working places.